RESPONSE OF SOME SYNTHETIC MAIZE CULTIVARS TO MINERAL, ORGANIC AND BIO FERTILIZER 1 – Yield and its components - & Al-Temimi, Al-Hilfy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this study was to investigate the possibility of replacing part of mineral fertilizers, by organic or bio fertilizers and effect of these fertilizers on grain yield and its components of maize (Zea mays L.). Field experiment was conducted at Abu Ghraib Research Station (Baghdad) during spring and fall seasons of 2016 using a randomized complete block design arranged in split plot with three replications .Three synthetic varieties of maize (Fajr 1 , Baghdad 3 and Sumer) in the main plots and nine fertilizer treatments which were : 100% NPK as recommended, NPK + sulfur, NPK + organic fertilizer, NPK + Bio fertilizer, NPK + Humic acid,50% NPK + sulfur,50% NPK + organic fertilizer,50% NPK + Bio and50% NPK + Humic acid in the sub plots . The results showed that the varieties Baghdad 3 gave highest value for most yield components for both seasons. 100% NPK+ organic fertilizers was superior in grain yield and most components (No. of ears per plant, No. of rows per ear, No. of grain per row and grain yield) most the combination between Fajir 1 and 100%NPK + organic fertilizers gave the highest grain yield about 10.381, 11.758 m h-1 respectively.